(untitled) - Gerhardt, Michael J. (Oxford, 2008)
The role that precedent plays in constitutional decision making is a perennially divisive subject among scholars of law and American politics. The debate rages over both empirical and normative aspects of the issue: To what extent are the Supreme Court, Congress, and the executive branch constrained by precedent? To what extent should they be? Taking up a topic long overdue for comprehensive treatment, Michael Gerhardt connects the vast social science data and legal scholarship to provide the most wide-ranging assessment of precedent in several decades.
Keywords: Stare decisis,Law; Interpretation and construction; United States,United States